Stone age transitions. Neolithisation in central Scandinavia - Knutsson, Helena (Documenta Praehistorica, 2003)
A summary of a series of individual research projects focused on the processes from the Mesolithic to the Late Neolithic in central Scandinavia. The projects were embeded in the "Coast to Coast project". The historicity in this process was emphasised.
Keywords: archaeology; arheologija; mezolitik; neolitik; Scandinavia; Skandinavija; neolitizacija; lovsko-nabiralske skupnosti; kmetovalci